Idiotism Capitalism and the Privatisation of Life - Curtis, Neal (Pluto Press, 2012)
Idiotism examines society in late capitalism where the market logic of neoliberalism has become the new 'common sense'. Using the Greek word idios, meaning 'private', Neal Curtis calls this privatisation of the world 'idiotism'. Through constructing a new vocabulary with which to understand our society, Curtis examines 'idiotism' across the spheres of economics, politics and culture, drawing on the philosophy and political theories of Martin Heidegger, Louis Althusser, Franco Berardi, Jacques Rancière and Cornelius Castoriadis. This book recasts our conception of the new privatised world's 'common sense', presenting it as not simply a case of false consciousness, but an problem related to our own existence.